PBL-Based Science Modules Integrating Ethno-STEM and Augmented Reality: An Analysis of Practicality and Effectiveness - Amanah, Prelia Dwi; Rahayu, Satutik; Gunawan, Gunawan (Department of Physics Education, Universitas Mataram, 2025)
This study aims to analyze the practicality and effectiveness of a Problem-Based Learning (PBL)-based science module integrated with the Ethno-STEM approach and assisted by Augmented Reality (AR) on the subject of Motion and Force for seventh-grade junior high school students. The module was developed as an innovative effort to improve the quality of science learning by linking local cultural contexts and the use of technology. This research uses research and development (R&D) methods including testing practicality and effectiveness. Documents analyzed for practicality include observation sheets for learning implementation, observation sheets for critical thinking skills and digital literacy through LKPD, and questionnaires for teacher and student responses. The effectiveness of the documents analyzed includes the results of pre-tests and post-tests for critical thinking skills and digital literacy of students. Practicality was analyzed using the % practicality formula, and the results of the analysis showed that all components obtained a % practicality value > 60%, which is categorized as practical and very practical. Meanwhile, the effectiveness test used N-Gain, where the N-Gain of critical thinking skills showed a value of 72.41% for the average %N-Gain of the experimental class and 53.83% for the control class. The N-Gain of digital literacy had an average of 68.71% for the experimental class and 24.24% for the control class. Therefore, the PBL model science module based on Ethno-STEM assisted by AR has proven to be practical and effective for use in the learning process at the junior high school level, so that the module can be trusted to be used as a learning resource.